Optimizing Craft Learning Experiences Through Mobile Learning Media Development with iSpring Suite: Solutions to Barriers to Student Understanding in Learning - Kurnia, Ulfa Isni; Lathifah, Afra; Urfan, Izzan Muhammad; Sholihah, Farasyatun Danis (Yayasan Keluarga Guru Mandiri, 2025)
Craft learning is an essential component of the education curriculum; however, students often encounter challenges in understanding and applying craft concepts effectively. This study aims to address these barriers by developing mobile learning media using iSpring Suite, leveraging its interactive features to enhance student engagement and comprehension. The research adopts the Instructional Development Institute (IDI) model, ensuring a structured approach to integrating instructional design, technology, and craft content. A quasi-experimental method was employed, involving pre-test and post-test assessments to measure learning improvements among students. The findings indicate that students who utilized the iSpring Suite-based mobile learning media demonstrated significantly higher comprehension and engagement levels than those using traditional lecture methods. A paired sample t-test (p 0.05) with an N-gain analysis revealed a moderate improvement (0.50) and an effect size analysis (1.80), confirming a substantial impact on learning outcomes. These results suggest that mobile learning media can effectively bridge gaps in craft education by providing flexible access to materials and fostering interactive learning experiences. The study contributes to educational technology by highlighting the potential of mobile learning in vocational and skill-based education, offering insights for further research and implementation in diverse learning contexts.